Approaches for utilization of natural gas - Ruwaida, Abdul Rasid; Nafees, A. (2018)
Oil and gas industry produces excess amount of associated and non - associated natural gas in exploration, drilling, transportation and processing of oil and gas. A significant percentage of these gases are wasted by burning, venting and flaring. A cleaned, purified and stabilized natural gas is subsequently used for industrial applications. The end use of the natural gas varies from being a feed stock in a fertilizer plant, combustion fuel for power generation to petrochemical and speciality chemical applications [1]. This research study looks into approaches and categories of natural gas utilization in conventional and unconventional methods. The aim is to understand natural gas utilization pattern to identify possible current and future natural gas usage than can be enhanced and optimised.